Upper Airway Dimensions among Different Skeletal Malocclusions: A Retrospective Observational Study by Cephalometric Analysis - Maria Francesca Sfondrini; Simone Gallo; Maurizio Pascadopoli; Paola Gandini; Caterina Roncoroni; Andrea Scribante (MDPI AG, 2024)
The aim of the present work was to investigate the upper airway dimensions in adult non-orthodontic patients, equally divided according to their skeletal class. Methods: In this retrospective cross-sectional study, lateral cephalometric radiographs of adult patients referred for orthodontic consultation were collected. Cephalometric tracing was performed with dedicated software. For each measure, descriptive statistics were calculated. Cephalometric measurements between the different skeletal classes were compared. Linear regressions were performed between upper airway diameters and cephalometric measurements, sex and age. Significance was predetermined for p < 0.05. Results: Lateral cephalometric radiographs of 120 patients were reviewed. Nasopharynx length (NL) and depth (PD) measurements were significantly shorter in skeletal class III patients (p < 0.05). The superior pharyngeal airway space (SPAS) was found to be significantly shorter in class III patients as compared to class II patients (p < 0.05), and the mean airway space (MAS) of class I patients was found to be significantly shorter compared to class II patients (p < 0.05). Palate length (PL) values were found to be significantly longer in class I (p < 0.05). Linear regressions showed that the sella-nasion-A point angle (SNA) and Riedel's angle between point A, the nasion and point B (ANB) significantly influenced NL and PD (p < 0.05). Conclusions: Class III patients show significantly shorter nasopharynx measurements; clinicians should consider that this sagittal discrepancy could be related to an altered anatomy of the upper respiratory tract.